Social Impact Assessment of Transportation Projects by Benefit or Damage Cost Analysis - A., Zulkiple; Norlela, Ismail; Mohd Sufian, Abdul Karim (2005)
Benefit/damage cost analysis is one of the alternative tools considered in the Trans-Simpact 2000 for Klang Valley. It is derived from the project evaluation technique that measures the benefit or damage cost of a project. The study involves with the formulation of the benefit or damage cost analysis model for SIA from two selected utility functions namely linear and CES. The CES utility function is found to be the best form to measure noise impact from an airport project in Osaka, Japan. The application of the utility function however, will require the calibration by the linear utility function.